Contro frate Bernardino da Siena. Processi al maestro Amedeo Landi (Milano 1437-1447) - Benedetti, Marina; Danelli, Tiziana (Milano University Press, 2021)
The volume Contro Bernardino. Processi al maestro Amedeo Landi is the result of the discovery of unpublished documentation on the trials - only partly known - against the abacus master Amedeo Landi, who taught the Milanese merchants at the Broletto. This is an exceptional case not only because only one witness to the activity of the Milanese inquisitorial court in the Middle Ages (whose documentation has been entirely lost) was known until now, but also because of the role of the ecclesiastical court and its officials. The wealth of information and themes has prompted a team effort by the professors of the Department of Historical Studies to clarify the many aspects (political, religious, economic, documentary) of an event that shows the vitality of 15th-century Milan, in which the protagonist, the teacher Amedeo Landi, in an attempt to protect his students, clashes with the most important preacher of his time, Brother Bernardino of Siena, whose canonisation process is temporarily blocked precisely to shed light on the Milanese episode.